Edukasi Masyarakat Sebagai Upaya Peningkatan Pemahaman Mengenai Thaharah Bagi Muslimat Desa Kebonrejo Kediri - Jian Nurus Shofa; Miksan Ansori (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2022)
The decline of science in Islam was marked by the division of power and empire in the 12th century to the 18th century. "Most people will not believe it even if you (Prophet Muhammad) really want it" Surah Ar-Ra'd. Purity from hadats and najis is a condition for the validity of a Muslim in carrying out certain worship. The author intends to hold the filling of Thaharah material in the Kebonrejo community. So that they understand the importance of taharah in daily worship. There are so many benefits that can be taken from Taharah, one of which is proof that Islam attaches great importance to cleanliness and purity. In the study itself the author chose to use the PAR (Participatory Action Research) method. The use of individual teaching activities can increase the spirit of discussion and problem solving, and the application of this method causes the learning process to be diverse. This extended approach will lead to a diversity of learning processes, and this diversity will be a wealth of knowledge that requires further study